Anxiety levels, precautionary behaviours and public perceptions during the early phase of the COVID-19 outbreak in China: a population-based cross-sectional survey. Issue 10 (8th October 2020) - Qian, Mengcen; Wu, Qianhui; Wu, Peng; Hou, Zhiyuan; Liang, Yuxia; Cowling, Benjamin J; Yu, Hongjie
Abstract : Objective: To investigate psychological and behavioural responses to COVID-19 among the Chinese general population. Design, setting and participants: We conducted a population-based mobile phone survey between 1 February and 10 February 2020 via random digit dialling. A total of 1011 adult residents in Wuhan (n=510), the epicentre and quarantined city, and Shanghai (n=501) were interviewed. Proportional quota sampling and poststratification weighting were used. Multivariable logistic regression models were used to investigate perception factors associated with the public responses. Primary outcome measures: We measured anxiety levels using the 7-item Generalised Anxiety Disorder Scale (GAD-7) and asked respondents to report their precautionary behaviours before and during the outbreak. Results: The prevalence of moderate or severe anxiety was significantly higher (p<0.001) in Wuhan (32.8%) than Shanghai (20.5%). Around 79.6%–88.2% residents reported always wearing a face mask when they went out and washing hands immediately when they returned home, with no discernible difference across cities. Only 35.5%–37.0% of residents reported a handwashing duration above 40 s as recommended by the WHO. The strongest predictor of moderate or severe anxiety was perceived harm of the disease (OR 1.8, 95% CI 1.5 to 2.1), followed by confusion about information reliability (OR 1.7, 95% CI 1.5 to 1.9). None of the examined perception factors were associated with odds of handwashing duration above 40 s. Conclusions: Prevalence of moderate or severe anxiety and strict personal precautionary behaviours was generally high, regardless of the quarantine status. Our results support efforts for handwashing education programmes with a focus on hygiene procedures in China and timely dissemination of reliable information.